2003
DOI: 10.1016/s1044-0305(03)00327-1
|View full text |Cite
|
Sign up to set email alerts
|

MS2Assign, automated assignment and nomenclature of tandem mass spectra of chemically crosslinked peptides

Abstract: In a previous report (Young et al., Proc. Natl. Acad. Sci. U.S.A. 2000, 97, 5802-5806), we provided a proof-of-principle for fold recognition of proteins using a homobifunctional amine-specific chemical crosslinking reagent in combination with mass spectrometry analysis and homology modeling. In this current work, we propose a systematic nomenclature to describe the types of peptides that are generated after proteolysis of crosslinked proteins, their fragmentation by tandem mass spectrometry, and an automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

17
376
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(396 citation statements)
references
References 26 publications
17
376
0
3
Order By: Relevance
“…Once distinguished and identified, collisionally activated dissociation (CAD) experiments on these species are performed to sequence the peptide or peptides. Structural assignment of the crosslinked peptides is still not routine despite the emergence of several sequencing algorithms [17][18][19][20][21][22]. In fact, one of the main pitfalls of mass spectrometric strategies for examination of crosslinked peptides is the lack of comprehensive rules for interpretation of the product ion spectra.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Once distinguished and identified, collisionally activated dissociation (CAD) experiments on these species are performed to sequence the peptide or peptides. Structural assignment of the crosslinked peptides is still not routine despite the emergence of several sequencing algorithms [17][18][19][20][21][22]. In fact, one of the main pitfalls of mass spectrometric strategies for examination of crosslinked peptides is the lack of comprehensive rules for interpretation of the product ion spectra.…”
mentioning
confidence: 99%
“…Despite the enormous number of investigations that have elucidated the fragmentation pathways of conventional tryptic peptides, to date only a few studies have focused on mapping the dissociation trends of crosslinked peptides in a systematic fashion [20,23,24]. Initial work by Schilling et al demonstrated that dissociation of intermolecularly crosslinked peptides typically resulted in amide bond cleavage of one peptide, with the crosslink and second peptide acting as a modification [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using these 15 constraints it was possible to assign the FGF2 to the correct ␤-trefoil fold family, from among a large set of structures predicted using threading techniques. The name MS3D has been proposed for the study of protein 3-dimensional structure using chemical cross-linking and mass spectrometry [5].All of the subsequent recent work published on intra-molecular cross-linking for MS3D studies has employed similar, commercially available primary amine selective reagents that can cross-link lysine residues to other lysine residues or the amino terminus [6 -10]. In our own recent work, we showed that a top down approach to the localization of cross-links using FTMS could be applied to localize three cross-links in ubiquitin [7], and in a more recent publication we showed that the distance constraints can be improved by using a series of cross-linkers of different lengths [6].…”
mentioning
confidence: 99%
“…Using these 15 constraints it was possible to assign the FGF2 to the correct ␤-trefoil fold family, from among a large set of structures predicted using threading techniques. The name MS3D has been proposed for the study of protein 3-dimensional structure using chemical cross-linking and mass spectrometry [5].…”
mentioning
confidence: 99%